The Influence Of Superset Training Model And Circuit Training On Fat Mass Changes And Muscle Mass Increase In Men - Kamaludin, Kamaludin; Subarjah, Herman; Pitriani, Pipit (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the difference in the effect of superset and circuit training models on changes in fat mass and increased muscle mass in men. Penelitian ini menggunakan metode eksperimen. The research design used in this study is an experimental The Randomized Pretest-Posttest Control Group design. The sample of this study amounted to 20 men, In this study the sample was selected using the Purposive Sampling technique on members of SOSI SPORT CLUB Bandung City. Collecting data in this study using Karada Scan Body Composition HBF‑375. Statistical calculations in testing the hypothesis were carried out using SPSS 21.0 with Independent Sample T-Test testing to see a comparison between the experimental group and the control group. The results of data analysis and calculations reveal that there is an effect of superset training on reducing fat mass, There is an effect of superset training on increasing muscle mass, There is an effect of circuit training on reducing fat mass, There is an effect of circuit training on increasing muscle mass, There is a difference in the effect of the comparison of superset and circuit training models on fat mass reduction, There is a difference in the effect of the comparison of superset and circuit training models on increasing muscle mass. The conclusion of this study is that the superset and circuit training models have an effect on reducing fat mass and increasing muscle mass in men.